Microstructure, wear and friction behavior of AISI 1045 steel surfaces coated with mechanically alloyed Fe16Mo2C0.25Mn/Al2O3-3TiO2 powders - Elazig, Cihan Ozel; Akgun, Gokcen; Gurgenc, Turan (Carl Hanser Verlag, 2017)
The surface of AISI 1045 steel was coated using the flame spray technique. Iron-based superalloy (Fe16Mo2C0.25Mn) powders were used as matrix material and a mixture of mechanically alloyed 10 wt.-% Fe16Mo2C0.25Mn and 90 wt.-% Al2O3-3TiO(2) powders was used as reinforcing material. The mechanical alloying process was performed by milling with an attritor for 60 hours. The coating material comprised of a mixture of the matrix (Fe16Mo2C0.25Mn) powder and mechanically alloyed reinforcing powders at varying rates of 5, 10 and 15 %, respectively. The microstructure, microhardness, adhesive wear behaviors and the coefficients of friction of the coated specimens were examined. It was observed that defects increased and cracks formed on the interface, depending on the increase in the reinforcing ratio. It was determined that the coefficient of friction and wear loss increased by the increasing load in all specimens. The minimum wear loss was observed for the specimen with 10 % reinforcement and the maximum wear loss was observed for the specimen with 15 % reinforcement. The highest average coefficient of friction by the applied load was obtained for the coating with 10 % reinforcement and the lowest average coefficient of friction was obtained for the specimen with 5 % reinforcement.
Keywords: Mechanical alloying; flame spray; Al2O3-3TiO(2); surface coating; wear